Pregabalin alleviates the nitroglycerin-induced hyperalgesia in rats. (22nd January 2015) - Di, W.; Zheng, Z.-Y.; Xiao, Z.-J.; Qi, W.-W.; Shi, X.-L.; Luo, N.; Lin, J.-W.; Ding, M.-H.; Zhang, A.-W.; Fang, Y.-N.
Highlights: Pregabalin pretreatment alleviates NTG-induced hyperalgesia. Pregabalin pretreatment suppresses peripheral CGRP release. Pregabalin pretreatment inhibits TGVS activation. Abstract: The association between the clinical use of nitroglycerin (NTG) and migraine suggests NTG as an animal model trigger for migraine. NTG-induced hyperalgesia in rats has been extensively used as a migraine model for pre-clinical research. Pregabalin is an anti-epileptic drug and may play a role in the preventive treatment of migraine; however, the mechanism of this action remains to be clarified. Herein, we performed the present study to investigate the effect of pregabalin on the NTG-induced hyperalgesia in rats. Sixty male Sprague–Dawley rats were divided equally into six groups. Thirty minutes before NTG injection, the rats were pretreated with pregabalin. von Frey hair testing was employed to evaluate tactile sensitivity. Enzyme-linked immunosorbent assay was used to analyze plasma calcitonin gene-related peptide (CGRP) levels in the jugular vein. Immunohistochemistry was applied to detect c-Fos-immunoreactive neurons and western blot was performed to detect c-Fos protein expression in trigeminal nucleus caudalis (TNC). We found that pregabalin pretreatment alleviated the NTG-induced hyperalgesia. Moreover, pregabalin suppressed peripheral CGRP release, c-Fos-immunoreactive neurons and the protein expression of c-Fos in TNC as well. These data suggest that pregabalin could alleviate the NTG-induced hyperalgesia. Further studies are required to determine the mechanisms of action for this effect.